2020
DOI: 10.1111/pbr.12821
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term trends and genetic architecture of seed characteristics, grain yield and correlated agronomic traits in triticale (×Triticosecale Wittmack)

Abstract: The aim of this study was to investigate long‐term genetic trends and the genetic architecture of grain yield, seed characteristics and correlated agronomic traits in triticale. Therefore, a panel of 846 diverse triticale genotypes was assessed for three agronomic and three seed shape‐ and size‐related traits. We observed a high genotypic variation and a high heritability for all traits. Analysing the development of these traits during the last decades revealed a continuous increase for grain yield and thousan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…Previous studies (Neuweiler et al 2020(Neuweiler et al , 2021Trini et al 2021) have reported grain yield, thousand-kernel weight and plant height based on the same field experiment. For the other traits, the Bonferroni-Holm test was used for outlier detection (Bernal-Vasquez et al 2016).…”
Section: Phenotypic Data Analysismentioning
confidence: 96%
“…Previous studies (Neuweiler et al 2020(Neuweiler et al , 2021Trini et al 2021) have reported grain yield, thousand-kernel weight and plant height based on the same field experiment. For the other traits, the Bonferroni-Holm test was used for outlier detection (Bernal-Vasquez et al 2016).…”
Section: Phenotypic Data Analysismentioning
confidence: 96%
“…The genetic architecture of grain yield and protein content has been investigated in many studies for wheat (Groos et al, 2003;Nigro et al, 2019;Reif et al, 2011) and rye (Hackauf et al, 2017;Mahone et al, 2013;Miedaner et al, 2012). For triticale, grain yield has already been studied in this large diversity panel (Neuweiler et al, 2020) as well as in other studies (Liu et al, 2016(Liu et al, , 2017.…”
Section: Complex Genetic Architecture Of the Selection Indicesmentioning
confidence: 99%
“…The most frequently used equipment of this type for the determination of wheat grain dimensions is likely the Marvin seed analyser (e.g. Gegas et al, 2010;Neuweiler et al, 2020;Sanchez-Bragado et al, 2020). Taking advantage that grains of modern cultivars do not vary appreciably in shape (Gegas et al, 2010), a single equation might be generated to transform the dimensions taken from 2-D images of individual grains into their dry weights that could be reasonably valid across genotypes and growing conditions.…”
Section: Introductionmentioning
confidence: 99%